Acute kidney injury associated with COVID-19: understanding its underlying mechanism - Singh, Samir (Applied Science and Technology Annals, 2020)
World Health Organization (WHO) has declared coronavirus disease 2019 (COVID-19) outbreak as a global emergency. Kidney involvement is commonly seen in COVID-19 patients with clinical findings ranging from mild proteinuria to acute kidney injury (AKI) in hospitalized patients. In this viewpoint, I would like to discuss about various mechanism contributing to AKI such as, entry of novel coronavirus into host cell, cytokine storm that destroy kidney tissues, increased blood clotting that clogs kidney, and probable direct infection of the kidney.